4CPS-233 Analysis of drug prescriptions of incompatible drugs through drug utilisation review. (March 2019) - Kim, H; Min, S; Yu, S; Jung, Y; Jeong, H
Abstract : Background: The Drug Utilisation Review (DUR) notifies alerts to clinicians and pharmacists when contraindicated drugs have been prescribed and dispensed. If clinicians want to override alerts, they must input reasons for not changing drugs. Pharmacists dispense prescriptions and inform patients using reasons provided by the clinician. Purpose: The purpose of this study was to confirm cases when contraindicated drugs have been prescribed overriding alerts, and to investigate prescriber's reasons for overriding drug-drug interaction alerts. Material and methods: This study investigated outpatient cases where contraindicated medications with drug-drug interaction were prescribed and administered unaltered, through the DUR, using the Electronic Medical Record, at this centre from 1 January 2018 to 30 June 2018. Prescriptions of identical medications for the same patient, prescribed on a different day, were regarded as a different case, due to having a different reason for issuing a prescription. Results: A total of 514 cases of prescriptions having contraindicated medications of drug-drug interaction were confirmed. The grounds for prescribing 514 cases of contraindicated medications include: unadministered contraindicated medications (220 cases, 42.8%); drugs taken intermittently or pro re nata (PRN) (147, 28.6%); administered by a clinical decision (79, 15.4%); local administration (21, 4.1%); meaningless words(44, 8.6%); and emergency medication (three, 0.6%). The reasons for prescribing contraindicated medications with drug-drug interaction in cases of anti-diabetic agents with CT contrast medium were as follows: unadministered contraindicated medications(95 cases, 76.0%), meaningless words (22, 17.6%) and administered by a clinical decision (eight, 6.4%). Reasons for other genitourinary organ and rectal agents with vasodilator were PRN (54 cases, 38.3%), administered by a clinical decision (42, 29.8%), unadministered contraindicated medications (29, 20.6%) and meaningless words (16, 11.3%). Reasons for NSAID with other cardiovascular drugs were PRN (65 cases, 69.9%), unadministered contraindicated medications (16, 17.2%) and local administration (13, 28.9%). Conclusion: We confirmed that certain medications were sometimes prescribed using an incorrect reason. Some clinicians input a reason that was something other than a PRN drug use, or entered a meaningless words. It is necessary to improve the system of entering the reasons why clinicians prescribe contraindicated drugs. References and/or acknowledgements: We acknowledge the assistance of Soojeong Yoon. No conflict of interest.